The politics of English : a Marxist view of language - Holborow, Marnie (Sage, 1999)
The Politics of English offers a major reappraisal of the way in which language is both shaped by, and contributes to, social life. Taking a classical Marxist approach, the author provides a view of the ideological aspects of language.
Keywords: Language and languages -- Political aspects.; English language -- Political aspects.; Language and languages -- Philosophy.; Women -- Language.; Philosophy, Marxist.; Langage et langues -- Aspect politique.; Langage et langues -- Philosophie.; Femmes -- Langage.; Philosophie marxiste.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General.; English language -- Political aspects; Language and languages -- Philosophy; Language and languages -- Political aspects; Philosophy, Marxist; Women -- Language; Taalpolitiek.; Engels.; Politieke aspecten.; Englische Sprache -- Politik.; Politik -- Englische Sprache.